Efficient Synthesis of Diethyl, Dialkyl α-Hydroxy-propylenebisphosphonates and Related 5-Phosphonoyl-1,2-oxaphospholane 2-Oxides - Varga, Petra Regina; Belovics, Alexandra; Karaghiosoff, Konstantin; Szabó, Rita; Bősze, Szilvia; Drahos, László; Keglevich, György (Synthesis, 2023)
A series of new dialkyl α-diethylphosphonoylethyl-α-hydroxy-ethylphosphonates were prepared using the Pudovik reaction of the corresponding γ-oxophosphonate with dialkyl phosphites performed on the surface of Al2O3/KF. The adducts revealed unexpected reactivity in the attempted O-acylation reaction, and provided the corresponding 5-phosphonoyl-1,2-oxaphospholane 2-oxides. On treatment with Cs2CO3, instead of the expected rearrangement a cyclization reaction leading to the same ring products took place. Three of the phosphonoylethyl-α hydroxy-ethylphosphonates, along with two phosphonoylmethyl analogues revealed significant and selective anticancer effect on A431 cells, and occasionally, on PC-3 and MDA-MB 231 cells.
Keywords: γ-oxophosphonate; Pudovik reaction; α-hydroxy-propylenebisphosphonate; cyclization; phosphonoyl-1,2-oxaphospholane 2-oxide; anticancer effect